EFEKTIVITAS MODEL CIRCUIT LEARNING BERBANTU MEDIA DIORAMA MEMPENGARUHI MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK KELAS V - Dyah Saraswati; Sumarno Sumarno; Anggun Dwi (JURNAL SINEKTIK, 2020)
This research aimed to determine the effectiveness of circuit learning model assisted by diorama media for influencing the motivation and learning outcomes of class V on theme 7 at SDN Mangunharjo. This research used Pre-Experimental design, One Group Pretest-Posttest Design. The population of all class V students in SDN Mangunharjo numbered 35 by using nonprobality sampling techniques with saturated sampling types. The average score of pretest motivation was 60.17 and the posttest average was 80.53. The average value of the pretest of the results of learning outcomes is 57.94 and the posttest averages 84.34. This is evidenced by the results of the motivation t-test where tcount (14.31)> ttable (1.69). Calculation of t-test results of learning where tcount (13.28)> ttable (1.69). This is also supported by N-Gain motivation and learning outcomes that show criteria of moderate to high. The concluded that the circuit learning model assisted by diorama media effectively influences the motivation and learning outcomes of the fifth grade students of Mangunharjo Elementary School Semarang.